1997
DOI: 10.1111/j.1523-536x.1997.tb00347.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Discharge Pack Formula and Breast Pumps on Breastfeeding Duration and Choice of Infant Feeding Method

Abstract: Relative to other known influences on the choice of feeding method and on breastfeeding duration, discharge pack contents do not merit great concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…More problematic aspects of study quality within this group of studies were the lack of description of those lost to follow-up (31% of studies reported this adequately 112,167,170,178,179 ) and an imbalance in demographic characteristics between groups (38% of studies reported this 106,107,112,172,174,178 ); in addition, only two studies conducted analysis based on ITT. 173,174 Only five studies (25%) used a valid and reliable outcome measure.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…More problematic aspects of study quality within this group of studies were the lack of description of those lost to follow-up (31% of studies reported this adequately 112,167,170,178,179 ) and an imbalance in demographic characteristics between groups (38% of studies reported this 106,107,112,172,174,178 ); in addition, only two studies conducted analysis based on ITT. 173,174 Only five studies (25%) used a valid and reliable outcome measure.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…For both figures, answers of 'yes' represented the maximum possible level of quality. Therefore, in considering Figure 11, it can be seen that most studies recruited women at the same point in their pregnancies (88% 103,106,107,[167][168][169][170][171][172][174][175][176][177][178][179] ), had a follow-up period that was similar between groups (94% 103,106,107,112,167,168,[170][171][172][173][174][175][176][177][178][179] ) and long enough to detect important effects on outcomes of interest (100% 103,106,107,112,[167][168][169][170][171][172][173][174][175][176][177]…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations